2020
DOI: 10.24289/ijsser.759203
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of adult education: Andragogues as change agents

Abstract: The paper analyses andragogues as change agents in education. Starting from critical theory, andragogues have the potential to work within the curriculum redefinition framework by enabling participants in educational process to identify areas of knowledge deficits and build on prior knowledge. In addition to this change, they can carry out transformative learning in which the central category is critical reflection, i.e. the most important characteristic of adult learning. The aim of this paper is to point out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For example, the extensive ALPINE study (Research voor Beleid & PLATO, 2008) has revealed that the field of adult learning and education has been characterized by its fragmented trainings for its ALFs’ professional development. This finding has been also confirmed by country-specific studies within Europe, for example in Denmark and Sweden (Andersson et al., 2012; Milana & Larson, 2010), Estonia, Latvia, and Lithuania (Gedvilienė et al., 2018; Jõgi & Gross, 2009), Croatia (Čepić & Mašić, 2016; Kušić et al., 2015), Portugal (Paulos, 2015), Bulgaria, Cyprus, Greece, and Turkey (Zarifis, 2009).…”
Section: Adult Learning Facilitators’ Professional Developmentmentioning
confidence: 63%
See 1 more Smart Citation
“…For example, the extensive ALPINE study (Research voor Beleid & PLATO, 2008) has revealed that the field of adult learning and education has been characterized by its fragmented trainings for its ALFs’ professional development. This finding has been also confirmed by country-specific studies within Europe, for example in Denmark and Sweden (Andersson et al., 2012; Milana & Larson, 2010), Estonia, Latvia, and Lithuania (Gedvilienė et al., 2018; Jõgi & Gross, 2009), Croatia (Čepić & Mašić, 2016; Kušić et al., 2015), Portugal (Paulos, 2015), Bulgaria, Cyprus, Greece, and Turkey (Zarifis, 2009).…”
Section: Adult Learning Facilitators’ Professional Developmentmentioning
confidence: 63%
“…However, participation in these programmes is strongly dependent on individual decision (Buiskool et al., 2009; Milana & Larson, 2010; Przybylska, 2008; Research voor Beleid & PLATO, 2008); consequently, professional development of ALFs has been treated as an individual responsibility even though there should have been regulatory frameworks (Milana & Larson, 2010). This, indeed, has created the common situation that many ALFs enter into the field without any specialization in adult learning and teaching in numerous European countries (Čepić & Mašić, 2016; Gedvilienė et al., 2018; Kušić et al., 2015; Paulos, 2015; Research voor Beleid & PLATO, 2008).…”
Section: Adult Learning Facilitators’ Professional Developmentmentioning
confidence: 99%